The Impact of Regularization Policies on Health Access: Examining Female Venezuelan Migrants’ Access and Utilization of Healthcare Services in Colombia - Diana M. Bowser; Priya Agarwal-Harding; Brielle Ruscitti; Donald S. Shepard; Arturo Harker Roa (Health Systems & Reform)
The Venezuelan humanitarian crisis has led to the displacement of over 7.7 million migrants, with Colombia hosting around one-third. Colombia has been praised for its progressive policies for Venezuelan migrant integration, and the government’s Estatuto Temporal de Protección para Migrantes Venezolanos (ETPMV), introduced in February 2021, provides one of the region’s most comprehensive regularization policies, permitting 10 years of residency and access to social protection services, including health insurance. We assessed the impact of the ETPMV on self-reported health insurance enrollment and formal healthcare utilization using two telephone surveys with 4,423 female Venezuelan migrants in 2020 and 2023. We used a difference-in-differences methodological approach, accounting for differences in levels of migrant health system integration across municipalities measured by a municipal enrollment index derived from secondary data. We find that the ETPMV significantly increases health insurance enrollment for female Venezuelan migrants and that while uninsured individuals experience a significant decline in healthcare utilization from 2020 to 2023, insured individuals experience no significant change. Additionally, the effect of insurance varies by municipal enrollment index, with greater impacts of insurance in areas with lower levels of regularization and health insurance enrollment. These results highlight the success of ETPMV in enhancing access to healthcare for Venezuelan migrants, with insurance enrollment providing a protective effect against declines in healthcare utilization compared to uninsured individuals. These findings underscore the importance of comprehensive regularization policies to address migrant health needs, while emphasizing the importance of continued efforts toward integration.